The behavior and out-of-plane stability of slender RC walls - Lee, Sang Wook (2017)
Damage to reinforce concrete (RC) structural walls by two earthquakes in 2010 Chile and 2011 Christchurch of New Zealand showed that commonly used RC walls might not fail in the expected ductile response but the failure could possibly be initiated by out-of-plane buckling of the RC walls. The recent trend shows that slender, small height-to-thickness ratio, RC walls are frequently used in many countries. In fact, most slender RC walls showed the out-of-plane buckling in both earthquakes. Therefore, this paper presents the findings from an analytical and experimental study of two slender RC walls. The two walls specimens were subjected to axial load ratio (N/fcAg) of 0.06 and 0.12 respectively and lateral in-plane cyclic load to demonstrate a seismic activity. The two walls experienced out-of-plane buckling but in different magnitudes, and the damage due to out-of-plane buckling ultimately led the wall failure. The obtained data from the experimental program give new perspectives into the development of out-of-plane instability, in particular with regard to the effect of the axial load. The magnitude of the axial compression applied can affect the out-of-plane stability of slender RC walls greatly. This report reviews past researches on rectangular RC walls, and discusses the experimental and analytical studies of this project. The main findings are summarized, which could benefit the future studies on the seismic performance of slender RC walls.